A reflective study on the use of the one day one color method in memorizing the Quran - Arif Nugraha, Muhamad; Nuzul, Dinda Ainun; Qolbi, Satria Kharimul; S, Waway Qodratulloh (Universitas Negeri Yogyakarta, 2025)
The declining interest and consistency in memorizing the Quran among younger generations pose a serious challenge amidst digital disruption and academic pressure. This study reflects on the experiences of participants in the One Day One Color (O.D.O.C) program, a Quranic memorization method based on daily targets and visualized progress, designed to foster discipline and measurable spiritual engagement. A descriptive qualitative approach was employed using in-depth interviews with participants who had completed the program, to explore the cognitive, affective, and spiritual impacts of this method. The findings indicate that O.D.O.C effectively facilitates the formation of long-term memory structures, enhances intrinsic motivation, and strengthens emotional connections with Qur’anic verses. Although there is a decline in memorization intensity after the program ends, most participants demonstrate continued effort by adjusting their rhythm, integrating alternative methods, and leveraging technology. Memorization also serves as a reflective tool, a reinforcement of religious identity, and a form of emotional therapy. In conclusion, the O.D.O.C method is not only technically relevant but also has a transformative impact on character and spiritual development. Its success is contingent upon post-program support, including community engagement, strategic flexibility, and adaptive digital systems. This study recommends O.D.O.C as a promising methodological innovation in contemporary Qur’anic education.